The AMA handbook of business documents : guidelines and sample documents that make business writing easy - Wilson, K. (Kevin), 1958- (AMACOM, American Management Association, 2011)
Provides reference and guidelines for business document writing, and includes sample documents and examples for such documents as abstracts, proposals, press releases, and training manuals.